ISSUES OF APPLICATION OF TAX MECHANISMS IN THE USE OF WATER RESOURCES IN THE REPUBLIC OF UZBEKISTAN - Sodiq Boymuratov (Web of Journals Publishing, 2025)
In a market economy, the socio-economic development of any state, along with other factors, largely depends on the existing reserves of natural resources and the efficiency of their use. Therefore, in the economic policy pursued in Uzbekistan, great attention is paid to the effective use of the country's natural resources, in particular water resources. Since water resources are limited and most of them are not renewable, it is possible to achieve the opportunity to meet the unlimited needs of society through the effective and rational use of existing natural resources.